The role of lipooligosaccharide phosphorylcholine in colonization and pathogenesis of Histophilus somni in cattle - Elswaifi Shaadi F; Scarratt William K; Inzana Thomas J (Veterinary Research, 2012)
Abstract Histophilus somni is a Gram-negative bacterium and member of the Pasteurellaceae that is responsible for respiratory disease and other systemic infections in cattle. One of the bacterium’s virulence factors is antigenic phase variation of its lipooligosaccharide (LOS). LOS antigenic variation may occur through variation in composition or structure of glycoses or their substitutions, such as phosphorylcholine (ChoP). However, the role of ChoP in the pathogenesis of H. somni disease has not been established. In Haemophilus influenzae ChoP on the LOS binds to platelet activating factor on epithelial cells, promoting bacterial colonization of the host upper respiratory tract. However, ChoP is not expressed in the blood as it also binds C-reactive protein, resulting in complement activation and killing of the bacteria. In order to simulate the susceptibility of calves with suppressed immunity due to stress or previous infection, calves were challenged with bovine herpes virus-1 or dexamethazone 3 days prior to challenge with H. somni. Following challenge, expression of ChoP on the LOS of 2 different H. somni strains was associated with colonization of the upper respiratory tract. In contrast, lack of ChoP expression was associated with bacteria recovered from systemic sites. Histopathology of cardiac tissue from myocarditis revealed lesions containing bacterial clusters that appeared similar to a biofilm. Furthermore, some respiratory cultures contained substantial numbers of Pasteurella multocida, which were not present on preculture screens. Subsequent biofilm experiments have shown that H. somni and P. multocida grow equally well together in a biofilm, suggesting a commensal relationship may exist between the two species. Our results also showed that ChoP contributed to, but was not required for, adhesion to respiratory epithelial cells. In conclusion, expression of ChoP on H. somni LOS contributed to colonization of the bacteria to the host upper respiratory tract, but phase variable loss of ChoP expression may help the bacteria survive systemically.